Music Creations Sabda Hita | Kreasi Musik Sabda Hita - Ida Bagus Gede Angga Prabawa Manuaba (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Sabda Hita consists of two syllables. Sabda, which means sound or sound produced from friction by humans. While Hita, which means happiness, is owned to achieve prosperity. So broadly speaking, Sabda Hita implies the sound of joy humans create in a harmonious and harmonious relationship.